2004
DOI: 10.1111/j.1439-0426.2004.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of tilapias (Oreochromis spp.) introduced in Mexico: morphometric, meristic and genetic characters

Abstract: In Mexico, the tilapia Oreochromis provides one of the most important sources of animal protein and income in a wide variety of communities throughout the country, however, their culture and production face severe problems because of lack of management information. Evaluated in the present study is the degree of morphological, meristic and allozyme variation of two tilapia strains, two species and one hybrid from two important reservoirs in Mexico, two tilapia fry production farms (TFPF) and an experimental pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 18 publications
1
39
0
3
Order By: Relevance
“…Solomon et al (2015) recorded significant differences in the ratio HL / SL in wild (23.7) and cultured (26.6) populations of C. gariepinus. Similarly, Vreven et al (1998) and Barriga-Sosa et al (2004) indicated that the biggest differences between wild and cultured populations were presented at the head. The value of this relationship and other relationships between morphometric characters is closely linked to the species, so it is not surprising that differences can be registered between studies.…”
Section: Morphometric Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…Solomon et al (2015) recorded significant differences in the ratio HL / SL in wild (23.7) and cultured (26.6) populations of C. gariepinus. Similarly, Vreven et al (1998) and Barriga-Sosa et al (2004) indicated that the biggest differences between wild and cultured populations were presented at the head. The value of this relationship and other relationships between morphometric characters is closely linked to the species, so it is not surprising that differences can be registered between studies.…”
Section: Morphometric Charactersmentioning
confidence: 99%
“…Barriga-Sosa et al (2004), after analysing morphometric characters in natural and domesticated populations of Nile tilapia (Oreochromis niloticus), reported morphological differences among these populations. Likewise, Narváez et al (2005) found significant differences between the two populations (wild and cultured) of Oreochromis niloticus in northern Colombia; differences were attributed to food, environmental conditions and the type of habitat (wild and cultured).…”
Section: Morphometric Charactersmentioning
confidence: 99%
“…Different methods are used for identification but phenotype based on morphometric and meristic is considered as earliest and authentic methods for the identification of fish species in fish biology to measure discreteness and relationships among various taxonomic categories. There are many well documented morphometric studies which provide evidence for stock discreteness (Avsar, 1994;Haddon and Willis, 1995;Bembo et al, 1996;Anene, 1999;Turan, 1999;Zafar et al, 2002;Barriga-Sosa et al, 2004;Doherty and McCarthy, 2004;Naesje et al, 2004). Morphometric is the external measurements of an organism, while meristic counts means serial counts of body elements (Talwar and Jhingran, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of Nile tilapia, Oreochromis niloticus in aqua cultures is due to its spreading in most countries of the world [1]. It breads in captivity and wide variety of water conditions [2].…”
Section: Introductionmentioning
confidence: 99%